Multivalent Aptamer Approach: Designs, Strategies, and Applications - Zhong Wang; Xiuying Yang; Nicholas Zhou Lee; Xudong Cao (Micromachines, 2022)
Aptamers are short and single-stranded DNA or RNA molecules with highly programmable structures that give them the ability to interact specifically with a large variety of targets, including proteins, cells, and small molecules. Multivalent aptamers refer to molecular constructs that combine two or more identical or different types of aptamers. Multivalency increases the avidity of aptamers, a particularly advantageous feature that allows for significantly increased binding affinities in comparison with aptamer monomers. Another advantage of multivalency is increased aptamer stabilities that confer improved performances under physiological conditions for various applications in clinical settings. The current study aims to review the most recent developments in multivalent aptamer research. The review will first discuss structures of multivalent aptamers. This is followed by detailed discussions on design strategies of multivalent aptamer approaches. Finally, recent developments of the multivalent aptamer approach in biosensing and biomedical applications are highlighted.